KEDUDUKAN SURAT EDARAN MAHKAMAH AGUNG BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Prasetya, Vestwansan Dipa; Indra, Mexsasai; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Circular Letter itself is a policy regulation for several reasons, as seen from its form, Circular Letters do not have a formal form that is similar to laws and regulations in general. Generally, legislation has forming parts such as Naming, Opening, Body, and Closing. We have not found these parts in a Circular so that from the formal point of view we can assume that the Circular is not a statutory regulation. Second, in terms of naming "Circular", in the book Regarding the Law by Jimmly Asshidiqie Circular Letter is classified in policy rules or quasi legislationThe problem that the author made the basis of this research is how the position of the Supreme Court circular based on Law Number 12 of 2011 concerning the Formation of Laws and Regulations about the contents of the Supreme Court circular based on Law Number 12 of 2011 concerning the Formation of Laws and Regulations -invitation. The purpose of this study is to determine the position of the Supreme Court circular based on Act Number 12 of 2011 concerning the Formation of Legislation and to find out the contents of the Supreme Court circular based on Act Number 12 of 2011 concerning the Formation of Legislation .This type of research used by the author is normative legal research, also called doctrinal law research. This normative research is a study that discusses the principles of law, systematic law, the extent of legal synchronization, the history of law and comparative law.The results of this study are first. Article 8 Paragraph 2 of Law Number 12 Year 2011. The regulation is related to other functions, namely administration, advice, supervision, and justice. However, the author is of the opinion, to determine the location of SEMA in the hierarchy of statutory regulations, we must pay attention to certain things. First, only SEMA contents in accordance with the provisions in article 79 of the Supreme Court Act can be included in the hierarchy of statutory regulations, second, Article 5 of Law Number 12 of 2011 concerning Formation of Regulations states that the material contained in the regulations the legislation must reflect the principles of: Protection, Humanity, Nationality, Family, Nationality, Unity in Diversity, Justice, Equality in Law and Governance, Order and Legal Certainty and or Harmony, Harmony and BalanceKeywords: Circular, Supreme, Court